Direct insights into the electrochemical processes at anode/electrolyte interfaces in magnesium-sulfur batteries. (July 2018) - Hu, Xin-Cheng; Shi, Yang; Lang, Shuang-Yan; Zhang, Xing; Gu, Lin; Guo, Yu-Guo; Wen, Rui; Wan, Li-Jun
Abstract: Magnesium-sulfur (Mg-S) batteries are highly attractive because of their high theoretical energy density, low cost and safety features. However, severe capacity fading issues limit their development, which are greatly associated with reaction processes at electrode/electrolyte interfaces. Herein, we systematically studied the interfacial processes of Mg deposition/stripping in ether-based electrolytes at nanoscale by in situ atomic force microscopy (AFM). It can be directly observed the initial nucleation of bowl-like structure and deposition of crystallized Mg upon charge in tetraglyme (TEG) - based electrolyte, followed with uniform stripping process upon discharge. In contrast, the initial nucleation of bowl-like structure, fast stack of nanoparticles (NPs) and deposition of crystallized Mg upon charge can be observed in diglyme (DEG) - based electrolyte, followed with nonuniform stripping process upon discharge. Combined with in situ optical imaging, former system shows better reversibility upon cycle. The present results reveal a direct insight into the structure-reactivity correlation at anode/electrolyte interfaces, which provides deep understanding of the interfacial mechanism to guide the design and development of the high-energy Mg-S batteries. Graphical abstract: By electrochemical AFM investigation using different ether-based electrolytes, in situ Mg deposition /stripping processes can be directly monitored at anode/electrolyte interfaces in Mg-S batteries. The surface structure and dynamics directly affect the electrochemical behaviors, revealing the interfacial mechanism and guiding advanced design for Mg-S batteries.fx1 Highlights: The anode processes were studied systematically by in situ atomic force microscopy. The details of nucleation, growth and crystallization at nanoscale were captured upon charge. Nonuniform stripping processes in diglyme system with fast dynamics were demonstrated. It shows better reversibility on Mg anode in tetraglyme system than in diglyme system upon cycle.